Effect of chemical admixtures on properties of high-calcium fly ash geopolymer - Rattanasak, Ubolluk; Pankhet, Kanokwan; Chindaprasirt, Prinya (International journal of minerals, metallurgy and materials, 2011)
Owing to the high viscosity of sodium silicate solution, fly ash geopolymer has the problems of low workability and rapid setting time. Therefore, the effect of chemical admixtures on the properties of fly ash geopolymer was studied to overcome the rapid set of the geo-polymer in this paper. High-calcium fly ash and alkaline solution were used as starting materials to synthesize the geopolymer. Calcium chloride, calcium sulfate, sodium sulfate, and sucrose at dosages of 1wt% and 2wt% of fly ash were selected as admixtures based on concrete knowledge to improve the properties of the geopolymer. The setting time, compressive strength, and degree of reaction were recorded, and the microstructure was examined. The results show that calcium chloride significantly shortens both the initial and final setting times of the geopolymer paste. In addition, sucrose also delays the final setting time significantly. The degrees of reaction of fly ash in the geopolymer paste with the admixtures are all higher than those of the control paste. This contributes to the obvious increases in compressive strength.